REINSTALASI POWER SUPPLY AREA LABORATORIUM AIRFIELD GROUND LIGHTING DI SEKOLAH TINGGI PENERBANGAN INDONESIA - Suse Lamtiar S (Langit Biru: Jurnal Ilmiah Aviasi, 2018)
To support the operation of electricity facilities in STPI Curug in general and especially in the lab of course TLB that require the availability of various facilities and equipment. In addition to basic facilities, there are also supporting facilities such as lighting facilities, visual aid and AGL, vehicle parking facilities, maintenance facilities in general and other facilities that directly or indirectly support STPI-Curug Airport Electricity Engineering activities. This qualitative research involves analysis of electrical power supply system in terms of quantity which includes the capacity of electric power supply prepared, as well as the availability aspect of electrical power supply from PLN is 630VA and the existing capacities is 80KVA while the standby genset capacities needed is 150KVA from the existing capacities this time is 80KVA, electrical power system analysis seen from the aspect of voltage and frequency stability, and plan to reinstall the power supply in the environment STPI laboratories including replacement of Genset Power Cable, Distribution Panels and other fittings. With the results of this study, it is useful to improve the supply of electrical power supply in STPI Curug, improve service to all electric users in STPI Curug, and encourage and improve the smoothness of lecture and laboratory activities at STPI Curug